2006
DOI: 10.1080/13576280600938232
|View full text |Cite
|
Sign up to set email alerts
|

Development and implementation of a nutrition education program for medical students: A new challenge

Abstract: The ten-hour nutritional workshops within the clinical weeks were well-received by second-year medical students. Using cases relevant to the students' age seems to enhance their interest in the program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(40 citation statements)
references
References 20 publications
0
40
0
Order By: Relevance
“…In the four evaluation-only studies, 37,52,55,60 self-report measures of knowledge suggested increases in students' understanding about obesity and nutritional risk 55 and the biopsychosocial approach to patient care. 37 Students also reported improvements in their counseling skills, 37 general research skills, 60 and attitudes (being more open to the topic of behavior change).…”
Section: Before-and-after Studies (N = 3; 25%)mentioning
confidence: 96%
See 3 more Smart Citations
“…In the four evaluation-only studies, 37,52,55,60 self-report measures of knowledge suggested increases in students' understanding about obesity and nutritional risk 55 and the biopsychosocial approach to patient care. 37 Students also reported improvements in their counseling skills, 37 general research skills, 60 and attitudes (being more open to the topic of behavior change).…”
Section: Before-and-after Studies (N = 3; 25%)mentioning
confidence: 96%
“…54,57 One study (8%) had a qualitative design, 61 whereas the other 11 (92%) employed the following quantitative designs: controlled trial (nonrandomized), 53,54,56,57 before-andafter study, 38,58,59 or evaluation-only study (no preintervention data obtained). 37,52,55,60 Of these quantitative-design studies, 7 (64%) did not, therefore, include control groups. Table 2 provides additional details about study characteristics.…”
Section: Study Characteristicsmentioning
confidence: 97%
See 2 more Smart Citations
“…Such a guide may better inform radiation oncologists on nutrition issues regarding cancer patients. In reference to internet classes or workshops, Endevelt et al [31] found 10-hour nutritional workshops to be effective at teaching nutrition education and well received by medical students. Therefore, nutrition education via medical school, published booklets, and inclusion of in-service workshops may prove to be beneficial in improving nutrition knowledge of future and practicing radiation oncologists.…”
Section: Discussionmentioning
confidence: 98%